PENGARUH SHOPPING LIFESTYLE, FASHION INVOLVEMENT, PRE-DECISION STAGE, DAN POST-DECISION STAGE TERHADAP IMPULSE BUYING BEHAVIOR - Muhrim Muhrim; Alida Palilati; Patwayati Patwayati (Pascasarjana Universitas Halu Oleo, 2018)
This study aimed to: 1) determine and analyze the simultaneously effect of shopping lifestyle, fashion involvement, pre-decision stage, and post-decision stage on shoppers’ impulse buying behaviors in Kendari city; 2) determine and analyze the effect of shopping lifestyle on shoppers’ impulse buying behaviors in Kendari city; 3) determine and analyze the effect of fashion involvement on shoppers’ impulse buying behaviors in Kendari city; 4) determine and analyze the effect of pre-decision stage on shoppers’ impulse buying behavior in Kendari city; 5) determine and analyze the effect of pos-decision stage on shoppers’ impulse buying behavior in Kendari city.Population of the study was shopper’s in Kendari city who exhibited impulse buying behavior at Matahari Departement Store and Lippo Plaza in Kendari. Since the exact number of the population was unknow, sample size was determined using the Unknow Population formula and accidental Sampling technique. Data of he study were analized using the multiple linear regression on the SPSS ver. 22.Results of the showed that: 1) simultaneously, shopping lifestyle, fashion involvement, pre-decision stage, and post-dicision stage had a positive, significant effect on shoppers’ impulse buying behaviors; 2) shopping lifestyle had a positive, significant effect on shoppers’ impulse buying behaviors; 3) fashion involvement had a positive, significant effect on shoppers’ impulse buying behaviors; 4) pre-decision stage had a dominant, positive, and significant effect on shoppers’ impulse buying behaviors; 5) post-decision stage had a positive, significant effect on shoppers’ impulse buying behaviors.Keywords: shopping lifestyle, fashion involvement, pre-decision stage, post-decision stage, impulse buying behavior